Absorption anisotropy studies of polymethine dyes - Lepkowicz, R.; Przhonska, Olga; Stryland, E.; Slominsky, Yu.; Kachkovski, A.; Mayboroda, Elena; Bondar, Nikolai (My University, 2004)
The determination of the spectral position of the excited states and orientation of the transition dipole moments of polymethine molecules is experimentally measured using two methods: the steady-state fluorescence anisotropy method, and a two-color polar¬ization-resolved pump-probe method. This novel use of the pump-probe method is described in detail and a comparison to the flu¬orescence method is given. Quantum-chemical modeling on the effects of the bridge structure in the polymethine chromophore on the linear absorption spectrum is also discussed.
Keywords: polarization; anisotropy; absorption state; polymethine dye; зондування; поляризація; дипольний момент; анізотропія; стан поглинання; поліметинові барвники; кафедра харчової хімії